Synthesis of Cristobalite Containing Ordered Interstitial Mesopores using Crystallization of Silica Colloidal Crystals. Issue 3 (23rd December 2020) - Matsuno, Takamichi; Nakaya, Takamichi; Kuroda, Yoshiyuki; Wada, Hiroaki; Shimojima, Atsushi; Kuroda, Kazuyuki
Abstract: Cristobalite with ordered interstitial dual‐sized mesopores was synthesized through the crystallization of silica colloidal crystals composed of monodispersed amorphous silica nanoparticles. An aqueous solution containing both a flux (Na2 O) and a carbon precursor (an aqueous low‐molecular weight phenolic resin) was infiltrated into the interstices of silica colloidal crystals. The organic fraction in the nanocomposite was further polymerized and subsequently carbonized in an Ar flow at 750 °C to reinforce the colloidal crystal structure. The thermal treatment resulted in the crystallization of the colloidal crystals into cristobalite while retaining the porous structure. The cristobalite‐carbon nanocomposite was calcined in air to remove the carbon and create interstitial ordered mesopores in the cristobalite. The surfaces of crystalline mesoporous silica are quite different from those of various ordered mesoporous silica with amorphous frameworks; thus, the present findings will be useful for a precise understanding and control of the interfaces between the mesopores and silica networks. Abstract : Ordered mesoporous cristobalite was successfully synthesized through the crystallization of silica colloidal crystals using a Na2 O flux in carbon matrices. The interstitial mesopores were well retained after crystallization. The present synthesis method is useful for the control of both the mesoporosity and crystallinity of various types of silica.